Associação de trombocitopenia e neutropenia aloimune - Silva, Leandra Christina Nogueira da [UNIFESP] (2018)
Background: Neonatal alloimmune trombocytopenia ( NAIT) results from feto maternal platelet antigen incompatibility leading to the production of maternal antibodies and destruction of fetal platelets during pregnancy. Similarly neonatal alloimmune neutropenia (NAN) is caused by maternal alloimmunization to incompatible fetal neutrophil antigens followed by transplacental transfer of the maternal antineutrophil antibody causing fetal or neonatal neutropenia. Although there are many reports in the literature describing these rare disorders, the simultaneous occurrence of NAIT and NAN has not been systematically evaluated. Aim: To study the incidence of simultaneous NAIT and NAN and to investigate prevalence and specificity of HPA, HNA and HLA antibodies when these syndromes happen concomitantly. Methods: Previous study of NAN included samples from 10,000 unselected neonates born in 4 obstetric units in Sao Paulo City (Brazil). From this cohort, we selected 1 9 cases (20 neonates ( 02 t wins) and 19 mothers) of simultaneous neonatal thrombocytopenia ( platelet<150x109/L) and neutropenia (neutrophil<2.0X109/L). HPA (HPA111, 15), HNA (HNA1, 3) and HLAI genotyping was per formed i n t he samples of mothers and neonates by PCRSSP, PCRRFLP and beadbased technology (Micro SSO, OneLambda; IDHPAXT, Grifols). HPA, HNA and HLA antibodies were investigated in maternal serum by ELISA (LAT Mixed, One Lambda; PaK12G, Immucor), MAIPA, beadbased a ssay (PAKLx, Immucor; LABScreen Multi, LABScreen Single, One Lambda) and granulocyte agglutination test (GAT). Results: The frequency of simultaneous neonatal thrombocytopenia and neutropenia showed in this study was 0 .2% ( 20/10,000 neonates). Among the 1 9 cases studied 15/19 (78.9%) showed feto-maternal incompatibility for platelet and/or neutrophil antigens: HPA1 3/15 (20.0%), HPA2 3/15 (20.0%), HPA3 5/15 (33.3%), HPA5 4/15 (26.6%), HPA9 1/15 (6.7%), HNA1a 1/15 (6.7%), HNA1b 3/15 (20.0%), HNA1c 2/15 (13.3%), HNA3 2/15 (13.3%). Antibody screening showed 3/19 (15.7%) samples with antiHPA (1 antiHPA5b, 1 antiHPA5a and 1 ant iHPA9bw), 10/19 (52.6%) samples with antiHLA class I, and 3/19 (15.7%) samples with antiHNA (2 antiHNA2; 1 antiHNA2/ 3b). Concerning the 3 samples with antiHPA antibodies, 2/3 (66.7%) also presented an antiHNA2 antibody, one of which with multiple antibodies (antiHPA5b, ant iHNA2, ant iHNA3b and ant iHLA). Among these 02 samples positive to HNA and HNA antibodies, 01 sample was reffering to 02 twins, resulting in 3/10,000 (0.03%) neonates with simultaneous TNAI and NAN. Among the samples positive to antiHLAI, 6/10 (60.0%) presented only HLA antibodies; HLA genotyping of m other/neonate confirmed at least o ne antigen/antibody matching. Conclusion: The incidence of simultaneous occurrence of NAIT and NAN was 0.3%. In contrast to the literature that describes antiHPA1 and ant iHNA1 as the most common antibodies involved in NAIT and NAN, in this study we found antibodies against HPA5, 9 and HNA2, 3. Although the role of antiHLAI antibodies in NAIT and NAN is controversial, interestingly we found 6/19 (31.6%) cases of simultaneous occurrence of neo natal thrombocytopenia and neutropenia presenting o nly HLAI specific antibodies. This data suggest that antibodies antiHLA can be considered as an etiology of TNAI e NAN.